جريمة الأمن السيبراني في انتهاك خصوصية البيانات والمعلومات وتحديد المسؤولية القانونية في دولة الإمارات دراسة وصفيه تحليلية: Cybersecurity Crime in Violating the Privacy of Data and Information and Determining Legal Liability in the UAE: A Descriptive and Analytical Study - Mohammed Hassan Merdad Obaid; Norfadhilah Binti Mohamad Ali; Ahmad Zaki Bin Salleh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث تهدف الدراسة إلى معرفة الاختراقات والهجمات السيبرانية والاعتداء على الخصوصية المعلوماتية في للبيانات والمعلومات الشخصية وخاصة السرية منها، عبر الاطلاع الكلي أو الجزئي على تلك الأسرار وهذا الاطلاع يكون في ذاته غير مشروع وان يتم من شخص لا يملك قانونا ترخيصاً بالولوج إلى تلك المعلومات، واعتمد البحث على المنهج الوصفي التحليلي الاستقرائي الذي يعتمد على جمع البيانات والحقائق عن الظاهرة وعرض أبعادها من الناحية النظرية والعلمية مع المنهج المقارن لفهم مهام القانون الإلكتروني جراء الاختراقات والانتهاكات التي تتعرض لها المؤسّسات ذات البيانات الخاصة، بهدف الوصول الى نتائج موضوعيه تحقق الهدف من الدراسة، من أهمها هي ما يميز جريمة الاختراق السيبراني هي أنها جرائم سريعة التنفيذ عن بعد دون اشتراط التواجد في مسرح الجريمة وأن الجريمة الالكترونية شكلت عنصر إغراء للمجرمين في إمكانية استغلال التكنولوجيا والتقنية الحديثة خصوصاً عندما يكون الجاني موظفاً يعتمد على الحاسب الآلي في طبيعة عمله بحيث يكون لديها كافة المعلومات اللازمة لتحقيق اختراقات متعددة ومتتالية لأنظمة الحاسب الآلي، والحاجة لوجود طرق حماية قوية للمعلومات المخزنة في أجهزة الحاسوب أو وسائط نقل البيانات الاكترونية بجدران الحماية، وخرج البحث بتوصيات اهمها تخصيص واستحداث مادة قانونية خاصة في قانون الجرائم الإلكترونية وحماية البيانات، تجرم استخدام أنظمة الاختراق السيبراني في جريمة اختراق الأنظمة المعلوماتية العامة والخاصة. ABSTRACT The study aims to know about cyber penetrations and attacks on information privacy in personal data and information, especially confidential ones, through complete or partial access to those secrets. This access is illegal if it is done by a person who does not legally have a license to access that information. the research relied on the descriptive analytical inductive approach, which relies on collecting data and facts about the phenomenon and presenting its dimensions theoretically and scientifically with the comparative approach to understand the tasks of electronic law as a result of the hacks and violations suffered by institutions with private data, with the aim of reaching objective results that achieve the goal of the study. The most important of them is that what distinguishes the crime of cyber hacking is that it is a crime that is quickly carried out remotely without requiring presence at the crime scene and that cybercrime constitutes an element of temptation for criminals in the possibility of exploiting technology and modern technology, especially when the perpetrator is an employee who relies on the computer in the nature of his work so that he has all The information necessary to achieve multiple and successive penetrations into computer systems, and the need for strong protection methods for information stored in computers or electronic data transmission media with firewalls, The research came up with recommendations, the most important of which is allocating and creating a special legal article in the Cybercrime and Data Protection Law that criminalizes the use of cyber-hacking systems in hacking public and private information systems.